PENGARUH PENERAPAN STRATEGI NUMBERED HEAD TOGETHER UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN FIKIH KELAS VIII DI MTS DARUL IHSAN HAMPARAN PERAK - Uway Jwairiyah (Universitas Islam Negeri Sumatera Utara Medan, 2017)
This study aims to explain how the influence of the implementation of the strategy Numbered Head Together to improve motivation and student learning outcomes on the subjects Fikih class VIII in MTs Darul Ihsan Hamparan Perak. The method used in this research is quantitative method by using Quasi Experiment approach which is meant to know the existence or effect of something that is imposed on the sample that is student. Based on the result of data analysis of research about influence of Numbered Head Together strategy toward motivation and result of student learning hence got some conclusion that is: the use of learner strategy Numbered Head Together influence to result learn student, where there are difference of result of student learning shown from result of result hypothesis test postes result Student learning using t test. In addition to influencing the learning outcomes strategy Numbered Head Together also affects the motivation of student learning based on the indicated from the results of t count calculation on student motivation questionnaire after being treated with the acquisition of significance value (Sig.) Of 0.04 and H0 rejected. The difference of students' motivation and student learning result before and after using the strategy of Numbered Head Together on the subject of fasting material of Ramadhan. The Numbered Head Together Strategy also causes a significant increase in students' learning motivation. This can be seen from the quite high difference between the mean score of students' learning motivation before being treated with the students' learning motivation after treatment. Students have a good response to the strategy of Numbered Head Together in improving motivation and student learning outcomes on the subject of material fikih Ramadan fasting. Increased motivation and student learning outcomes after using the Numbered Head Together strategKeywords: influence, strategy, numbered head, together, motivation, learning outcomes